Aquaporin‐mediated transport: Insights into metalloid trafficking. Issue 3 (17th June 2022) - Handa, Neha; Gupta, Pawan; Khanna, Kanika; Kohli, Sukhmeen Kaur; Bhardwaj, Renu; Alam, Pravej; Ahmad, Parvaiz
Abstract: Metalloids in plants have diverse physiological effects. From being essential to beneficial to toxic, they have significant effects on many physiological processes, influencing crop yield and quality. Aquaporins are a group of membrane channels that have several physiological substrates along with water. Metalloids have emerged as one of their important substrates and they are found to have a substantial role in regulating plant metalloid homeostasis. The present review comprehensively details the multiple isoforms of aquaporins having specificity for metalloids and being responsible for their influx, distribution or efflux. In addition, it also highlights the usage of aquaporin‐mediated transport as a selection marker in toxic screens and as tracer elements for closely related metalloids. Therefore, aquaporins, with their imperative contribution to the regulation of plant growth, development and physiological processes, need more research to unravel the metalloid trafficking mechanisms and their future applications.